COMPASSION CHARACTER IN MULTITHEORY PERSPECTIVE - Chairunnisa, Vinda (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2021)
This study aims to describe the concept of compassion character which was analyzed based on the perspective theory by Krstin D. Neff, Paul Gilbert, and Elisha Goldstein. This analysis was intended to produce a synthesis formula that comprehensively includes definition, essence, aspect, and indicators of compassion character. This study applied for a literature review with a descriptive analysis technique. The function of this analysis result is as the basis for designing instruments to measure the compassion character more comprehensively and following the Indonesian context.Â